Upaya Indonesia dalam Menangani Permasalahan Perdagangan Manusia di Benjina Kepulauan Aru Maluku - Permatasari, Tavera; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Human trafficking in the fishing industry is one of the threats of human security and also tothe security of Indonesia’s sea. PT. Pusaka Benjina Resources (PBR) conducts its activities by illegally employing ABK in the territorial waters of Indonesia. This study aims to explain the efforts of Indonesia as the main actor in addressing human security issues. In this regards, the Indonesian government involved IOM as a non-state actor to solve human trafficking problems in Benjina. To analyze these efforts, this study uses the concept of human security, the theory of state-centric, and the concept of rational actors. This research uses a qualitative research methodology based on data collection through a literature study. The results show that the Indonesian government’s efforts in dealing with human trafficking by PT. PBR were divided through handling the defendant according to UU No. 21 Tahun 2007 and the victim handled with assistance that facilitated by IOM.